Student Empowerment Agenda Kelab Orators initiatives in developing communication and public speaking skills for UMPSA students - Amy Zulaikha, Mohd Ali; Jochen, Venason (UMPSA, 2024)
PEKAN, 9 March 2024 – In the ever-evolving landscape of technology and innovation, effective communication serves as the cornerstone for success in various fields.